2009
DOI: 10.1073/pnas.0811350106
|View full text |Cite
|
Sign up to set email alerts
|

Resolving cadherin interactions and binding cooperativity at the single-molecule level

Abstract: The cadherin family of Ca 2؉ -dependent cell adhesion proteins are critical for the morphogenesis and functional organization of tissues in multicellular organisms, but the molecular interactions between cadherins that are at the core of cell-cell adhesion are a matter of considerable debate. A widely-accepted model is that cadherins adhere in 3 stages. First, the functional unit of cadherin adhesion is a cis dimer formed by the binding of the extracellular regions of 2 cadherins on the same cell surface. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
197
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(205 citation statements)
references
References 42 publications
6
197
1
1
Order By: Relevance
“…4b); Poisson statistics predicts that under these conditions, 497% of measured events occur because of the rupture of single X-dimers. Single-molecule fluorescence microscopy experiments have previously shown that under similar experimental conditions, a majority of the measured unbinding events occur because of rupture of single trans-dimers 29 . Approximately 1,000-2,000 single-molecule measurements were carried out at five different clamping forces.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…4b); Poisson statistics predicts that under these conditions, 497% of measured events occur because of the rupture of single X-dimers. Single-molecule fluorescence microscopy experiments have previously shown that under similar experimental conditions, a majority of the measured unbinding events occur because of rupture of single trans-dimers 29 . Approximately 1,000-2,000 single-molecule measurements were carried out at five different clamping forces.…”
mentioning
confidence: 85%
“…Biotinylated cadherin mutants were immobilized on glass coverslips and AFM cantilevers (Olympus, Model: TR400PSA) using methods described previously 29 . Briefly, the cantilevers and coverslips were cleaned and functionalized with amine groups using a 2% v/v solution of 3-aminopropyltriethoxysilane (Sigma) dissolved in acetone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…idea that a trans binding between cadherin monomers via their EC1 domains initiates their interactions (Zhang et al 2009). The calcium-sensitive sequences are highly conserved among the family members, whose sequences are the hallmarks for this family, and all classic cadherins show a similar calcium dependence.…”
Section: Cadherinsmentioning
confidence: 99%
“…Cell-cell adhesion is mediated principally by cadherins, which form Ca 2+ -dependent trans-interactions between opposed extracellular domains on adjacent cells and bind a cytoplasmic complex of β-catenin and α-catenin (14). Adhesion of E-cadherin-expressing MDCK epithelial cells to surfaces functionalized with EcadFc mimics this interaction, because the bridging chemistry correctly orients the N terminus of the E-cadherin extracellular domain outward while still allowing rotation and short-range lateral clustering of the protein (13,15).To simultaneously mimic cell binding to ECM and other cells, we used unique, functionalized micropatterned surfaces comprised of alternating stripes of ECM (collagenIV) and adjustable amounts of EcadFc. Recruitment of cellular proteins to different stripes was monitored with GFP-tagged proteins that had been previously well characterized (8, 16).…”
mentioning
confidence: 99%